Three-dimensional composite photocatalytic material, preparation method thereof and wastewater treatment system
By loading Fe3S4 particles in polyurethane materials, combined with the appropriate wastewater treatment system design, the problems of low photocatalytic efficiency and narrow photoresponse range are solved, efficient degradation of antibiotics is achieved, and sewage treatment efficiency is improved. Maintains the system's long-term stability.
Patent Information
- Application Number
- CN202411371465.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional wastewater treatment technology has limited ability to degrade antibiotics. The existing photocatalytic systems have problems with uneven light distribution and energy input in antibiotic wastewater treatment, resulting in low photocatalytic efficiency and difficult to apply on industrial scale.
Using three-dimensional composite photocatalytic materials, Fe3S4 particles are loaded in polyurethane materials, and reactive oxygen is generated through light-induced Fe2+ and Fe3+ redox cycles. Combined with polyurethane materials, the contact surface area between the catalyst and the pollutants is expanded, and an appropriate wastewater treatment system is designed to improve the Antibiotic degradation efficiency.
It realizes efficient degradation of antibiotics, improves sewage treatment efficiency, and maintains the long-term stable performance of the system through multi-stage reactor design and appropriate Fe3S4 load and flow rate control.
Smart Images

Figure CN119281400A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a three-dimensional composite photocatalytic material and a preparation method thereof and a wastewater treatment system. Background Art
[0002] Emerging contaminants (ECs) pose a major threat to aquatic ecosystems and human health, among which antibiotics are a rapidly growing emerging contaminant. Traditional wastewater treatment technologies have limited ability to degrade antibiotics, resulting in incomplete removal of drug residues, which are widely distributed in hospital sewage, medical wastewater, and even natural water bodies. Therefore, a low-cost and effective method is urgently needed to degrade antibiotics in hospital wastewater.
[0003] Photocatalysis, which can generate active free radicals under light irradiation, provides a promising route for efficient and economical antibiotic degradation. It has been reported that various antibiotics and refractory organic pollutants can be photocatalytically degraded with little or no additional chemical reagents. Although significant progress has been made in developing new photocatalytic materials and elucidating degradation mechanisms, bridging the gap between laboratory-scale studies and actual wastewater treatment remains a challenge. Currently, continuous flow photocatalytic systems have been used to treat gaseous pollutants such as CO2 and NO, but problems such as uneven light distribution and the need for external energy input have hindered their application in antibiotic wastewater treatment. The industrial-scale application of this system also requires careful consideration of factors such as characteristic light sources and reactor design. In this regard, appropriate bandgap photocatalysts that can utilize a wide range of visible light sources to excite carriers, as well as the ease of fabrication and scale-up of photocatalyst composites, are crucial to the overall system design.
[0004] Therefore, it is necessary to provide a three-dimensional composite photocatalytic material and its preparation method and wastewater treatment system to simplify the preparation steps of the photocatalytic material, solve the problems of narrow light response range and low photocatalytic efficiency of the photocatalytic material, and further improve the degradation efficiency of antibiotics in sewage. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a three-dimensional composite photocatalytic material and a preparation method and a wastewater treatment system, which simplify the preparation steps of the photocatalytic material, solve the problems of narrow light response range and low photocatalytic efficiency of the photocatalytic material, and further improve the degradation efficiency of antibiotics in sewage.
[0006] A first aspect of the present invention provides a three-dimensional composite photocatalytic material.
[0007] Specifically, it includes Fe3S4 particles and polyurethane materials;
[0008] The Fe3S4 particles are loaded in the polyurethane material;
[0009] The loading amount of the Fe3S4 particles is 5-25wt%.
[0010] Preferably, the Fe3S4 particles are in the shape of a flower cluster.
[0011] Preferably, the size of the Fe3S4 particles is 10 to 30 μm.
[0012] Further preferably, the size of the Fe3S4 particles is 20 to 30 μm.
[0013] More preferably, the size of the Fe3S4 particles is 25 μm.
[0014] A second aspect of the present invention provides a method for preparing a three-dimensional composite photocatalytic material.
[0015] Specifically, the following steps are included:
[0016] (1) polymerizing polyol, diphenylmethane diisocyanate, a blowing agent, a crosslinking agent, a catalyst and a surfactant to prepare a polyurethane foam;
[0017] (2) soaking the polyurethane foam in a Fe3S4 solution, and drying the soaked polyurethane foam to obtain a three-dimensional composite photocatalytic material;
[0018] The mass ratio of the polyol, diphenylmethane diisocyanate, foaming agent, crosslinking agent, catalyst and surfactant is 100: 25-35: 0.5-1.5: 0.4-0.6: 0.1-0.2: 0.35-0.45.
[0019] Preferably, the mass ratio of the polyol, diphenylmethane diisocyanate, blowing agent, cross-linking agent, catalyst and surfactant is 100: 25-30: 0.5-1: 0.45-0.55: 0.1-0.2: 0.35-0.4.
[0020] Further preferably, the mass ratio of the polyol, diphenylmethane diisocyanate, blowing agent, cross-linking agent, catalyst and surfactant is 100:30:0.9:0.5:0.1:0.4.
[0021] Preferably, in step (1), the polyol includes at least one of polyether polyol and polyurea polyol.
[0022] Preferably, in step (1), the surfactant includes at least one of silicone oil and nonyl acid.
[0023] Preferably, in step (2), the method for preparing the Fe3S4 solution comprises:
[0024] Ferric chloride hexahydrate and thiourea are dissolved in a solvent, stirred, heated, washed, and dried to obtain Fe3S4 particles, and then the Fe3S4 particles are dispersed in a solvent to prepare a Fe3S4 solution.
[0025] Preferably, in step (1), the foaming agent includes at least one of water, dichloromethane and chlorofluorocarbon.
[0026] Preferably, in step (1), the cross-linking agent includes 3,3-dichloro-4,4-diaminodiphenylmethane.
[0027] Preferably, in step (1), the catalyst comprises at least one of triethylenediamine, dimethylethanolamine and stannous octoate.
[0028] Preferably, in step (2), the soaking time is 3 to 8 minutes.
[0029] More preferably, the soaking time is 5 to 8 minutes.
[0030] More preferably, the soaking time is 5 minutes.
[0031] Preferably, in step (2), the concentration of the Fe3S4 solution is 100-500 mg L -1 .
[0032] Preferably, in step (2), the drying temperature is 70-90°C.
[0033] More preferably, the drying temperature is 75-85°C.
[0034] More preferably, the drying temperature is 80°C.
[0035] A third aspect of the present invention provides a wastewater treatment system.
[0036] Specifically, the wastewater treatment system includes the three-dimensional composite photocatalytic material provided in the first aspect.
[0037] Preferably, the reaction flow rate of the wastewater treatment system is 1 to 15 mL min -1 .
[0038] Preferably, the wastewater comprises antibiotic wastewater.
[0039] Preferably, the wastewater treatment system further comprises an LED light source, and the wavelength of the LED light source is 450-500 nm.
[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0041] The invention loads Fe3S4 particles with ordered charges into polyurethane materials to obtain a three-dimensional composite photocatalytic material having Fe 2+ and Fe 3+ Redox couple, light-induced Fe 2+ and Fe 3+ The continuous redox cycle promotes the generation of active oxygen, which is beneficial to the degradation of antibiotics. The polyurethane material expands the contact surface area between the three-dimensional composite photocatalytic material and the pollutant, which is more conducive to the mass transfer and diffusion of the catalyst interface, and enhances the interaction between pollutants and active oxygen to achieve the degradation of antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The XRD pattern of Fe3S4 particles prepared in the present invention;
[0043] Figure 2 This is a SEM image of Fe3S4 particles prepared in the present invention;
[0044] Figure 3 This is a schematic diagram of the preparation process of the three-dimensional composite photocatalytic material of Example 1 of the present invention;
[0045] Figure 4 It is a schematic diagram of the structure of the wastewater treatment system of Example 2 of the present invention and a diagram showing the efficiency of each module in degrading tetracycline;
[0046] Figure 5 The effect diagram of tetracycline degradation in wastewater treatment system constructed by three-dimensional composite photocatalytic materials with different Fe3S4 loading amounts;
[0047] Figure 6 This is a diagram showing the effect of the wastewater treatment system constructed in Examples 2 and 5 of the present invention on the degradation of tetracycline. DETAILED DESCRIPTION
[0048] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0049] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0050] Example 1
[0051] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0052] Catalytic material: composed of Fe3S4 particles and polyurethane material, wherein the Fe3S4 particles are loaded in the polyurethane material (ie, the Fe3S4 particles are located on the surface and inside of the polyurethane material), and the loading amount of the Fe3S4 particles is 25wt%.
[0053] The specific steps of the preparation method are as follows:
[0054] Fe3S4 particles were synthesized by wet chemical method. 3mmol FeCl3·6H2O and 5mmol thiourea were dissolved in 40mL ethylene glycol solvent and magnetically stirred for 20min to form a precursor solution containing iron and sulfur. Then, the solution was transferred to a 100mL Teflon-lined stainless steel autoclave and sealed and heated at 180°C for 12h. After the reaction, the black powder was washed with distilled water and anhydrous ethanol several times, placed in a vacuum drying oven, and dried at 60°C for 6h to obtain the final product, Fe3S4 particles. Figure 1 This is the X-ray diffraction spectrum (XRD) diagram of the prepared Fe3S4 particles. It can be seen that the position of the diffraction peak of the obtained Fe3S4 particles is consistent with that of the standard card, indicating that the synthetic material is indeed Fe3S4 particles. Figure 2 The scanning electron microscope (SEM) image shows that the prepared Fe3S4 particles are in the morphology of flower clusters and have a size of 25 μm.
[0055] Polyether polyol, diphenylmethane diisocyanate, water, 3,3-dichloro-4,4-diaminodiphenylmethane, dimethylethanolamine, and silicone oil are mixed in a mass ratio of 100:30:0.9:0.5:0.1:0.4, stirred, and poured into a specific mold for chemical reaction. After sufficient reaction and polymerization, demolding treatment is performed to obtain polyurethane foam. The preparation process diagram is shown in the figure. Figure 3 .
[0056] Then prepare 500 mg L -1 Fe3S4 solution is prepared, and the polyurethane foam is immersed in the solution for 5 minutes. After the Fe3S4 solution is completely absorbed, the immersed polyurethane foam is placed in a drying oven and dried at 80°C to obtain a three-dimensional composite photocatalytic material with a Fe3S4 particle loading of 25wt% (Fe3S4 loading (wt%) = m(Fe3S4) / m(polyurethane material)*100%).
[0057] Example 2
[0058] A wastewater treatment system.
[0059] A wastewater treatment system was constructed based on the three-dimensional composite photocatalytic material prepared in Example 1.
[0060] The wastewater treatment system uses three double-layer quartz tube nested reactors in series. The inner column of the reactor can be placed with an LED light source (wavelength of 500nm), and the annular sandwich space contains the three-dimensional composite photocatalytic material prepared in Example 1 and flowing wastewater. The fluid volume of each reactor is 163mL. The reactor material is quartz. The reaction flow rate of the wastewater treatment system is 1mLmin -1 The specific structure is as follows Figure 4 As shown in (a) in .
[0061] Example 3
[0062] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0063] The difference from Example 1 is that the concentration of the Fe3S4 solution is 100 mg L -1 , that is, a three-dimensional composite photocatalytic material with a Fe3S4 particle loading of 5wt% is obtained.
[0064] Example 4
[0065] A wastewater treatment system.
[0066] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Example 2.
[0067] Example 5
[0068] A wastewater treatment system.
[0069] The difference from Example 2 is that the reaction flow rate of the wastewater treatment system is 15 mL min -1 .
[0070] Comparative Example 1
[0071] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0072] The difference from Example 1 is that the concentration of the Fe3S4 solution is 75 mg L -1 , that is, a three-dimensional composite photocatalytic material with a Fe3S4 particle loading of 3.75wt% was obtained.
[0073] Comparative Example 2
[0074] A wastewater treatment system.
[0075] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 1.
[0076] Comparative Example 3
[0077] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0078] The difference from Example 1 is that the concentration of the Fe3S4 solution is 50 mg L -1 , that is, a three-dimensional composite photocatalytic material with a Fe3S4 particle loading of 2.5wt% is obtained.
[0079] Comparative Example 4
[0080] A wastewater treatment system.
[0081] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 3.
[0082] Comparative Example 5
[0083] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0084] The difference from Example 1 is that polyether polyol, diphenylmethane diisocyanate, water, 3,3-dichloro-4,4-diaminodiphenylmethane and dimethylethanolamine are mixed in a mass ratio of 100:30:0.9:0.5:0.1.
[0085] Comparative Example 6
[0086] A wastewater treatment system.
[0087] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 5.
[0088] Comparative Example 7
[0089] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0090] The difference from Example 1 is that polyether polyol, diphenylmethane diisocyanate, water, 3,3-dichloro-4,4-diaminodiphenylmethane, dimethylethanolamine, and silicone oil are mixed in a mass ratio of 100:30:0.9:0.5:0.1:0.2.
[0091] Comparative Example 8
[0092] A wastewater treatment system.
[0093] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 7.
[0094] Comparative Example 9
[0095] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0096] The difference from Example 1 is that polyether polyol, diphenylmethane diisocyanate, water, 3,3-dichloro-4,4-diaminodiphenylmethane, dimethylethanolamine, and silicone oil are mixed in a mass ratio of 100:30:0.9:0.5:0.1:0.6.
[0097] Comparative Example 10
[0098] A wastewater treatment system.
[0099] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 9.
[0100] Comparative Example 11
[0101] A three-dimensional composite photocatalytic material and a preparation method thereof.
[0102] The difference from Example 1 is that polyether polyol, diphenylmethane diisocyanate, water, 3,3-dichloro-4,4-diaminodiphenylmethane, dimethylethanolamine, and silicone oil are mixed in a mass ratio of 100:30:0.9:0.5:0.1:0.8.
[0103] Comparative Example 12
[0104] A wastewater treatment system.
[0105] The difference from Example 2 is that the annular interlayer space accommodates the three-dimensional composite photocatalytic material prepared in Comparative Example 11.
[0106] Performance testing:
[0107] Methods: During the experiment, 2.5 mL of solution was extracted from the system at specific irradiation time intervals and collected by filtration. The absorbance of the reaction solution was measured at a wavelength of 357 nm using UV-visible spectrophotometry to determine the tetracycline content.
[0108] The wastewater treatment system prepared in Example 2 of the present invention has the best removal rate of antibiotics. Figure 4 As shown in (b), the continuous flow experiment shows that although the efficiency of module 1 decreases by 50% after running for 30 hours, Figure 4As shown in (c) and (d), module 2 and module 3 maintain nearly 100% tetracycline degradation efficiency within 60h and 130h of system operation, respectively. This modular device design allows the catalyst to be regenerated in the deactivated module while maintaining the overall performance of the system. The wastewater treatment system promotes the effective degradation of pollutants by extending the contact time with the catalyst through a multi-stage reactor design. Polyurethane foam is used as a three-dimensional supporting material to fix the photocatalyst while maintaining light permeability. The three-dimensional polyurethane material structure also expands the contact surface area between the active photocatalyst and the pollutant, which is more conducive to mass transfer, diffusion control and pollutant degradation at the catalyst interface. The three-dimensional composite photocatalytic material prepared in Example 1 is integrated into a homemade continuous flow photocatalytic reactor, which can be used to efficiently treat tetracycline-contaminated wastewater (8.8ppm).
[0109] like Figure 5 As shown, the efficiency of tetracycline degradation of the system with different Fe3S4 loadings in Example 2, Example 4, Comparative Example 2 and Comparative Example 4 was tested. The experimental results show that with the increase of Fe3S4 loading, the degradation rate of tetracycline in each stage of the device is greatly improved. When the Fe3S4 loading in Example 2 is 25wt%, the degradation efficiency of tetracycline in the system is the highest, about 99%. The three-dimensional composite photocatalytic material with a loading of 3.75wt% in Comparative Example 2 increases the degradation rate of tetracycline by about 50% relative to the loading of 2.5wt% in Comparative Example 4, but it is still far lower than the degradation efficiency of 25wt% Fe3S4 loading.
[0110] like Figure 6 As shown, the degradation effect of the wastewater treatment system in Example 2 and Example 5 was tested. When the reaction flow rate was increased from 15 mL min -1 Reduced to 1 mL min -1 When the tetracycline residence time in the device was extended from 8min to 120min, the efficiency of photocatalytic degradation of tetracycline by the three-dimensional composite photocatalytic material increased from 90% to 99%. And after 6 cycles, the flow rate was 1mLmin -1 The degradation rate of tetracycline in the system was 98.3%, while the degradation rate of tetracycline in the system with a flow rate of 15 mL min-1 was 85.6%. This shows that the slower the flow rate, the longer the contact time between the pollutant and the catalyst, and the better the degradation effect.
[0111] The role of the surfactant is to reduce the surface tension of the mixed materials of the foaming system, so as to improve the miscibility between the components, adjust the size of the bubbles, thereby controlling the pore structure, improving the stability of the foaming, and preventing the occurrence of bubble collapse. The results show that in Comparative Examples 6 and 8, when the amount of silicone oil added is 0 or 0.2, it will cause bubble collapse or coarse pores. When the amount of silicone oil is increased to 0.4 in Example 2 of the present invention, good open-cell foam can be obtained. In Comparative Examples 10 and 12, when the amount of silicone oil continues to increase to 0.6 and 0.8 parts, the amount of silicone oil will be too high, and the closed-cell rate of the foam will be further increased, affecting the resilience and compression hardness of the foam, thereby reducing the degradation rate of antibiotics.
[0112] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.
Claims
1. A three-dimensional composite photocatalytic material, characterized in that: including Fe3S4 particles and polyurethane materials; The Fe3S4 particles are loaded in the polyurethane material; The loading amount of the Fe3S4 particles is 5-25wt%.
2. The three-dimensional composite photocatalytic material according to claim 1, characterized in that: The Fe3S4 particles are in the shape of a flower cluster.
3. The three-dimensional composite photocatalytic material according to claim 1, characterized in that: The size of the Fe3S4 particles is 10 to 30 μm.
4. The method for preparing a three-dimensional composite photocatalytic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) polymerizing polyol, diphenylmethane diisocyanate, a blowing agent, a crosslinking agent, a catalyst and a surfactant to prepare a polyurethane foam; (2) soaking the polyurethane foam in a Fe3S4 solution, and drying the soaked polyurethane foam to obtain a three-dimensional composite photocatalytic material; The mass ratio of the polyol, diphenylmethane diisocyanate, foaming agent, crosslinking agent, catalyst and surfactant is 100: 25-35: 0.5-1.5: 0.4-0.6: 0.1-0.2: 0.35-0.
45.
5. The preparation method according to claim 4, characterized in that: In step (1), the polyol includes at least one of polyether polyol and polyurea polyol.
6. The preparation method according to claim 4, characterized in that: In step (1), the surfactant includes at least one of silicone oil and nonyl acid.
7. The preparation method according to claim 4, characterized in that: In step (2), the preparation method of the Fe3S4 solution comprises: Ferric chloride hexahydrate and thiourea are dissolved in a solvent, stirred, heated, washed, and dried to obtain Fe3S4 particles, and then the Fe3S4 particles are dispersed in a solvent to prepare a Fe3S4 solution.
8. A wastewater treatment system, characterized in that: The wastewater treatment system comprises the three-dimensional composite photocatalytic material according to any one of claims 1 to 3.
9. The wastewater treatment system according to claim 8, characterized in that: The reaction flow rate of the wastewater treatment system is 1-15 mL min -1 .
10. The wastewater treatment system according to claim 8, characterized in that: The wastewater includes antibiotic wastewater.